HUBUNGAN KETAHANAN KELUARGA DAN PERAN TEMANSEBAYA TERHADAP PERILAKU KESEHATAN REPRODUKSIPADA REMAJA DI SMP NEGERI 258 JAKARTA - Salsa Billa Taftahzani, (2023)
Reproductive health issues such as promiscuous sex abortion, sexually, transmitted diseases, and HIV/AIDS continue to be a significant problem among young people that require government attention. One reason is low family resilience and peer influence. This study aimed to investigate the relationship between family resilience and the role of peers in adolescent reproductive health behaviors in SMP X Jakarta Timur. The study design uses a cross-sectional method and a proportional stratified random sampling technique. The participants in this study were adolescent who were still active in SMP X Jakarta. A total of 250 young people participated in this study. Chi-square test result showed that there is an association between family resilience and the role of peers in youth reproductive health with a p-value of family resilience of 0.002 (p<0.05); OR = 2.252 and the role of peers in 0.003 (p<0.05); OR = 2.166. The importance of this study lies in the need to optimize good reproductive health behaviors in adolescent. The researchers recommend this study to the DKI Jakarta Health Office as a policy basic to understand, assistance, and monitor parents on adolescent reproductive health and advise schools by providing counselling about choosing good peers.